Synthesis and characterization of gold nanoparticles using fruit extract of Crescentia cujete L - Fauzan Amin; Micha Mahardika; Nada Morisca (Jurnal Pendidikan Kimia (JPKim), 2019)
Nanoparticles play important role in biotechnology such as food and drug industries. Gold nanoporticles(Au-NPS) have been wdely used in any drug therapies like drug delivery system for cancer, tumor, and diabetes treatment. Recently, Au-NPS have been devoleped to increase drug selectivity between tumor and normal cells. In the present studies, we use the fresh fruit ekstract (FFE) of crescentia cujete L mediated blue green alga for the synthesis of Au-NPS. The characterization of Au-NPS was carried out by using UV-Vis spectroscopy, Fourier transform infrared spectroscopy (FTIR), and Transmission Electron spectroscopy (TEM). UV-VIS spectrometry indicated formation of nanoparticles which produces an intense absorbance peak at 531 nm. FTIR reveales the functional group involved in reduction and stabilization of Au-NPS. TEM have shown the morphology of Au-NPS with mean size 10,11 nm.Keywords: Crescentia cujete; gold nanoparticles; green alga